Breach-rhythm - M. B. Mironov; S. D. Burd; N. V. Kukina; Yu. V. Rubleva; O. O. Kordonskaya; I. V. Senko; A. V. Yurchenko; M. A. Bogomazova; R. T. Tairova; Kh. A. Dzhabrailova (Эпилепсия и пароксизмальные состояния)
Electroencephalography (EEG) is one of the main non-invasive methods for examining brain activity. Cranial defects caused by trauma or surgery can lead to artifacts on the EEG such as breach-rhythm. In this article we provide a literature-based definition, pathophysiological features of the breach-rhythm, differential diagnosis between breachrhythm and epileptiform activity, as well as our own clinical case of a patient with epilepsy and breach-rhythm.